An Introduction to Biomechanics - Humphrey, Jay D.; O’Rourke, Sherry L. (Springer, 2015)
We have very much appreciated the overwhelmingly positive response to this book by professors and students alike at universities across the USA and abroad. The goals and approach of this Second Edition thus remain as originally presented: to motivate the need for continuum biomechanics across diverse areas of study, to present a consistent introductory approach to the biomechanics of solids and fluids and their interactions, and to illustrate this general approach via numerous Examples and Exercises. This Second Edition has allowed us, however, to add new “Observations” that highlight further implications of mechanics within biology and medicine, to add a new Appendix, to update the references, to include additional Exercises, and to correct some typographical errors. Perhaps most importantly, this Second Edition has allowed us to add at the end of each chapter a “Chapter Summary” to help emphasize general points of importance as well as to reinforce the consistency of the big picture ideas across chapters. It was just over a decade ago that we wrote this book with great excitement and we are very pleased to report that research and training in biomechanics continues to be universally recognized as both exciting and vitally important. Traditional areas of research within biomechanics continue to contribute to basic science as well as translational research and development whereas new areas continue to emerge with great promise. For example, the US National Committee on Biomechanics (USNCB) recently sponsored three Frontiers Meetings that highlighted special opportunities for biomechanics in areas ranging from developmental biology to the fight against cancer and infections. Since the first printing of this book, the National Science Foundation has added another funding program entitled, Biomechanics and Mechanobiology, and a Federal Interagency Modeling and Analysis Group (IMAG), led by Grace Peng, Ph.D., has been established to emphasize across many funding agencies the importance of multiscale mathematical modeling in biology and medicine, which prominently includes biomechanics. Hence, in areas new and old alike, we continue to see the importance of the fundamentals of biomechanics in the formulation and solution of diverse biological and medical problems of importance. We thus continue to encourage the reader to focus on learning the fundamentals well and, of course, to enjoy the journey.
Solids and Fluids, Analysis and Design
Keywords: Biomechanics